PENGGUNAAN MODEL PEMBELAJARAN BERPIKIR, BERPASANGAN DAN BERBAGI (THINK PAIR SHARE) OLEH GURU MATA PELAJARAN AKIDAH AKHLAK DI MADRASAH IBTIDAIYAH AL-MUSLIMUN TIGARUN KECAMATAN AMUNTAI TENGAH KABUPATEN HULU SUNGAI UTARA: PENGGUNAAN MODEL PEMBELAJARAN THINK PAIR SHARE PADA MATA PELAJARAN AKIDAH AKHLAK DI MADRASAH IBTIDAIYAH - Ria Susanti (AL-ULUM | JURNAL PENDIDIKAN DAN PENGAJARAN, 2025)
This research aims to determine how the use of the think pair share learning model by the subject teacher of Akidah Akhlak at MI Al-Muslimun Tigarun, Amuntai Tengah District, Hulu Sungai Utara Regency. The type of research used is field research, while the research approach used is a qualitative research approach. The subjects of this study were grade VI students at MI Al-Muslimun Tigarun. While the object of this study is the use of the think pair share learning model by the subject teacher of Akidah Akhlak at MI Al-Muslimun Tigarun, Amuntai Tengah District, Hulu Sungai Utara Regency. The results of the study showed that the think pair share learning method in learning Akidah Akhlak at MI Al-Muslimun Tigarun was implemented systematically and effectively. Teachers play an active role as facilitators and mentors, while students show a positive response because this method helps shape social character. Despite the challenges, the implementation of this method has a positive impact on the learning process.